Security, privacy, and applied cryptography engineering : 6th international conference, SPACE 2016, Hyderabad, India, December 14-18, 2016 proceedings /: 6th international conference, SPACE 2016, Hyderabad, India, December 14-18, 2016 proceedings. (2016) - Unknown
No abstract available